2019
DOI: 10.1088/1757-899x/615/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Using calcium chloride as an accelerator for Portland pozzolan cement concrete compressive strength development

Abstract: The influence of calcium chloride (CaCl2) as an accelerator for the compressive strength development of concrete made with type I Portland pozzolan cement (PPC) as a hydraulic binder has been investigated. Natural sand and crushed stone were used as fine aggregate and coarse aggregate, respectively. The mix proportion of concrete, by weight, was 1.0 binder: 2.1 fine aggregate: 3.4 coarse aggregate and the water-binder ratio was 0.57. The calcium chloride added to the concrete mixture was 0%, 1.0%, 1.5%, and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…In another study [13], it was observed that the addition of 4% of CaCl 2 to three different types of OPC increased the compressive strength of concrete, which was cured at 7, 14, 21, and 28 days. Similarly, another study [14] revealed that as the concentration of CaCl 2 increased from 1% to 2%, the compressive strength of the OPC concrete also increased for curing durations of 1, 3, and 7 days. However, at Days 28 and 90, the cement samples gained the highest compressive strength at a CaCl 2 concentration of 1.5%, and the compressive strength decreased as the concentration of CaCl 2 increased to 2%.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In another study [13], it was observed that the addition of 4% of CaCl 2 to three different types of OPC increased the compressive strength of concrete, which was cured at 7, 14, 21, and 28 days. Similarly, another study [14] revealed that as the concentration of CaCl 2 increased from 1% to 2%, the compressive strength of the OPC concrete also increased for curing durations of 1, 3, and 7 days. However, at Days 28 and 90, the cement samples gained the highest compressive strength at a CaCl 2 concentration of 1.5%, and the compressive strength decreased as the concentration of CaCl 2 increased to 2%.…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, previous studies predominantly focused on concrete, where the composition of concrete is different to well cement [17,18]. Even though several studies have been conducted to study the influence of CaCl 2 on GPC, HPHT conditions were not adopted in their experimental work [14].…”
Section: Introductionmentioning
confidence: 99%
“…When calcium chloride is used as an accelerator admixture in the concrete, it increases the rate of hardening of the concrete [13,14]. ASTM C-494 requires a minimum increase of 125% over the control sample at age of 3 days.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…According to Butler, the calcium chlorides of low levels can hardly be responsible for major reinforced concrete distress. Some other researchers have concluded that CaCl2 does not significantly corrode rebar if the concrete is welldesigned and well-compacted and if the reinforcement concrete cover is suitable [14].…”
Section: Resistance To Corrosion Of Reinforcementmentioning
confidence: 99%
“…Selain itu kondisi ini juga dipengaruhi oleh relatif lebih lambatnya reaksi yang terjadi antara unsur reaktif dari ATC dengan kapur bebas yang dihasilkan SPI. Gejala lambatnya perkembangan kekuatan pada beton yang mempergunakan perekat hidrolik berupa campuran antara SPI dan abu terbang kelas F maupun berupa semen Portland pozzolan juga telah dilaporkan masing -masing oleh Salain (2017) dan Salain (2019). Seperti dinyatakan oleh Malhotra dan Ramezanianpour (1994) bahwa faktor-faktor penting yang mempengaruhi perkembangan kekuatan dan permeabilitas beton yang mempergunakan abu terbang yaitu properti dari abu terbang, komposisi kimia, ukuran partikel, reaktivitas, serta kondisi temperatur dan perawatan.…”
Section: Diskusiunclassified